Eighteenth-Century Magazine Illustration and Copper Plates Coloured from Nature - Anderson, Jocelyn (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2020)
In the second half of the eighteenth century, as the magazine publishing industry grew, illustrations became a fundamental element of magazines, and some of the most ambitious publishers began offering readers coloured illustrations. This article examines a series of coloured illustrations published in The Universal Magazine of Knowledge and Pleasure. Launched in 1752, this series depicts subjects from natural history, including birds, animals, and plants. These plates were a critical vehicle in adapting and circulating elite scientific publications to a wide and diverse audience. As material objects, they were challenging to produce, but they were very important to the magazine’s appeal to readers. Offering wondrous visual spectacles in print, the series entwined narratives of curiosity, natural history, exotic travel, and colonialism.